Teaching song leading – a conceptualization of strategies - Fündeling, Olivia; Stadler Elmer, Stefanie (Frontiers in Education, 2025)
Teacher educators play a key role in the training of generalist music teachers by imparting both musical and didactic knowledge about music teaching. The purpose of this article is to conceptualize and empirically document the strategies employed by an experienced music teacher educator when modeling song teaching for and with preservice teachers. Following an initial interview, we filmed the teacher demonstrating the teaching of two songs. Based on microanalyses of the teacher modeling song teaching, we identified five strategies: goal-directed continuity; working with examples; modeling, monitoring, and fading; generative elaboration; and striving for aesthetic form. Some of these teaching strategies are not clearly defined concepts but are rather prototypical and domain specific. By conceptualizing and empirically documenting the phenomena, we emphasize the need to expand and differentiate the technical terms generally used for teaching methods and strategies and to consider the specificity of the subject matter.